Gastroparesis in carcinoma gallbladder: a scintigraphic study - Rajapandi, Pitchai; Eakanathan, Adimoolam; Ravishankar, Jeyaraj (International Surgery Journal, 2018)
Background: Gastroparesis is characterized by delayed gastric emptying in the absence of mechanical gastric outlet obstruction. There is strong association of gastroparesis with carcinoma gallbladder. The aim of the study was to find out the incidence of delayed gastric emptying in carcinoma gallbladder and its correlation with symptoms of stasis and stage of the disease. Methods: Patients diagnosed with carcinoma gallbladder and their matched controls were included in this study. Patients with mechanical gastric outlet obstruction were excluded. All patients underwent contrast enhanced computer tomography scan and radio labeled (Technitium 99) solid meal Scintigraphy study. Normal gastric emptying time was calculated from control group as Mean +2SD. Results: 30 patients were matched with 20 controls after obtaining informed consent. Upper limit of gastric emptying time is 55.09 minutes. Adenocarcinoma was the commonest histological subtype (50%), abdominal pain was the commonest symptom (86.7%) and hepatomegaly was the commonest sign (46.7%), GETt1/2 for patients was 66.72±26.52 minutes while it was 40.53±7.28 minutes in controls (p <0.05). Gastroparesis increased with advancing stage of carcinoma gallbladder (p <0.05). Symptoms of gastric stasis were seen only in 15.6% of patients. Conclusions: Patients with carcinoma gallbladder can have gastroparesis without obvious symptoms of delayed gastric emptying. This delay in gastric emptying can be documented reliably using solid meal scintigraphic study even in patients without symptoms of gastroparesis. The pathophysiology of gastroparesis needs further study. It may be prudent to remember that while performing palliative bypass surgery for gastric outflow obstruction, that in patients with carcinoma gallbladder, the gastrojejunostomy may not function as expected due to delayed gastric emptying.